Transfer of Individual Micro‐ and Nanoparticles for High‐Precision 3D Analysis Using 360° Electron Tomography. Issue 1 (4th December 2017) - Przybilla, Thomas; Zubiri, Benjamin Apeleo; Beltrán, Ana M.; Butz, Benjamin; Machoke, Albert G. F.; Inayat, Alexandra; Distaso, Monica; Peukert, Wolfgang; Schwieger, Wilhelm; Spiecker, Erdmann
Abstract: A versatile approach is demonstrated, providing a general routine for an extensive and advanced 3D characterization of individually selected micro‐ and nanoparticles, enabling the combination of complementary and scale‐bridging techniques. Quintessential to the method is the transfer of individual particles onto tailored tips using a conventional scanning electron microscope equipped with a suitable micromanipulator. The method enables a damage‐ and contamination‐free preparation of freestanding particles. This is of significant importance for applications addressing the measurement of structural, physical, and chemical properties of specifically selected particles, such as 360° electron tomography, atom probe tomography, nano X‐ray tomography, or optical near‐field measurements. In this context, the method is demonstrated for 360° electron tomography of micro‐/macroporous zeolite particles with sizes in the micrometer range and mesoporous alpha‐hematite nanoparticles exhibiting sizes of 50–100 nm, including detailed pre‐ and post‐characterization on the nanoscale. Abstract : Particles with sizes in the nanometer to micrometer range are used in diverse fields of research and application. As the particle design rises in complexity, a detailed and correlative characterization of their properties becomes indispensable. A general and reliable routine is presented to precisely characterize the structural, physical, and chemical properties of individually selected micro‐ and nanoparticles in 3D.